PENGEMBANGAN E-MODUL INTERAKTIF BERTEMATIK BUDAYA CIREBON SEBAGAI BAHAN AJAR BERBASIS TEKS BAGI PEMELAJAR BIPA TINGKAT DASAR - Widianti, Nurhannah (CAKRAWALA LINGUISTA, 2023)
ABSTRACTThe aim of the research is to produce an interactive e-module with quick response codes on the Cirebon culture theme as basic level BIPA teaching material. The method used is research and development with the aim of producing a new product. There are two methods used, namely descriptive and evaluative research methods. The first step that researchers take in processing data is to describe and analyze it. The researcher reflects that what has been done is according to plan, then prepares the next design. The second step is discussing the data. Research shows that this e-module received a positive response from BIPA teachers and students. The results of the interviews showed that the teaching materials created were effective and utilized technological sophistication in the form of fast response codes. This makes BIPA students enthusiastic about learning the language and culture of Cirebon. The material is presented clearly. There are instructions for working and evaluating understanding using simple sentences. The appearance of this e-module is also interesting because it presents visualizations that fit the context and has a variety of colors so it is not monotonous. Research notes, namely that all stages of development must be carried out.